Pengelolaan Kelas dalam Meningkatkan Motivasi Belajar Siswa di SD Negeri Dawung, Tegalrejo, Magelang, Jawa Tengah - Sulastri, Sulastri (Prosiding University Research Colloquium, 2021)
This study was used to determine the real situation of classroom management at SD NegeriDawung, Tegalrejo, Magelang. The method used by the author in this study is a qualitativemethod. Data collection techniques aree interviewers, observation and documentation.Includes classroom management in the form of physical, including classrooms, table andchair arrangements, furniture and other learning tools and non physical related tostudents. Therefore educators have the main responsibility in schools, teachers are directlyinvolved in learning activities at the school, teachers have the task of shaping the characterof students in schools, helping students develop their talents and interests, and improvingthe quality of education in order to increase students motivation. Creative skilla in learningactivities during teaching and learning activities take place one way is by classroommanagement.